The Ethical Tension between Individual Autonomy and Public Responsibility in Proactive Health - Min CHEN (Yixue yu zhexue, 2025)
First, it discusses the ethical struggle between individual autonomy and public health responsibility, including the manifestation of the four principles of medical ethics in the allocation of health responsibilities, and the conflict between individualism and communitarianism. Second, it examines how social determinants of health place vulnerable groups at a disadvantage in terms of health, exploring the potential exacerbation of health inequalities by an excessive emphasis on individual responsibility. Next, using China's long-term care insurance policy as an example, the paper analyzes how this policy balances individual autonomy and social support in practice. Finally, possible ethical pathways and policy recommendations are proposed, advocating for a shift from "individual accountability" to "systemic empowerment", to achieve a more just and inclusive "Healthy China" strategy.